New records of deep-sea barnacles (Cirripedia: Thoracica: Scalpelliformes) from the Clarion-Clipperton region, Pacific Ocean - Poltarukha, Oleg P.; Mel’nik, Vyacheslav F. (Zootaxa, 2012)
Barnacles (Cirripedia: Thoracica) taken in the Clarion-Clipperton region, central Pacific, during cruises of the Research VesselYuzhmorgeologia (2003, 2006, 2007, 2010, 2011) were studied. Three species, Amigdoscalpellum torbenwolffi Zevina, 1981,Arcoscalpellum radiatum Rao et Newman, 1972 and Catherinum tortilum (Zevina, 1973), were collected in five samples from depths of 4680–4877m. The data obtained considerably extend the previously known distributions of these three species.